Restarting Homestay Business in Sri Lanka: Challenges in New Normal Conditions of COVID-19 Pandemic - Vindya Hewage; Ruwan Ranasinghe (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This research seeks to analyze the issues that have evolved for running homestays under the new normal conditions of the COVID-19 pandemic in Sri Lanka due to a dearth of studies that have been conducted to determine the rigorous pandemic consequences on homestays. Qualitative research approach was entrusted and direct in-depth interviews were conducted for a sample of sixteen homestay operators in Ella and Mirissa area of Sri Lanka which are popular for the homestay concept among foreign visitors. Thematic analysis was adopted consequently to achieve the research objectives. The study's findings reveal the economic, environmental, health and safety, and socio-cultural concerns that have surfaced. It specifically demonstrates that homestay operators are unwilling to take use of the domestic tourist industry in order to overcome financial difficulties, as well as their prejudice against local visitors and lack of preparedness to launch their operations owing to worries of virus transmission. The fear of respondents to express their opinions leisurely was evident due to the emergence of an extensive Covid wave at the time of data collection. Further, the study covered only two destinations in the island. The outcome of this study recommends the Sri Lankan policy makers to re-evaluate the existing guidelines and improve them further while using homestays as a post pandemic branding tool as “New Normal Homestay” concept